Optimalisasi Promosi Produk Dan Layanan Menggunakan Teknologi Internet Of Things Pada Toko Figo Mart - Rio Anggala; Tata Sutabri; Arif Hidayat (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
In the modern retail world, competition is getting tougher, and leveraging technology is key to enhancing competitiveness. One technology with great potential to optimize product and service promotions is the Internet of Things (IoT). Figo Mart, as one of the players in the retail industry, needs to utilize IoT to offer a more interactive and efficient shopping experience for its customers. This study aims to explore how IoT can be used to optimize product and service promotions at Figo Mart. The research method used is a qualitative approach with a case study at Figo Mart. The results of the study show that the implementation of IoT can improve the effectiveness of promotions, increase customer loyalty, and provide accurate data for consumer behavior analysis. IoT technologies such as smart sensors and mobile-based devices can be used to inform promotions in real time, offer product recommendations, and optimize customer service.